ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG DI PASAR SEGAR CINERE KOTA DEPOK - Soetjahjo, Matthew Samuel; Karmini, Ni Luh (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2025)
Economic development is not solely dependent on industrialization and government programs; the informal sector also plays a crucial role. Traditional markets not only function as distribution for basic necessities but also as local economic hubs that support the livelihoods of traders. However, traders face various challenges in their efforts to increase their income, such as limited access to capital, technology, and more. This research aims: 1) to analyze the simultaneous effect of capital, length of business, location, and e-commerce usage on the seller’s income at Pasar Segar Cinere Kota Depok; 2) to analyze the partial effect of capital, length of business, location, and e-commerce usage on the seller’s income at Pasar Segar Cinere Kota Depok. This research was conducted using multiple linear regression analysis technique. The result of the research is that capital, length of business, location, and e-commerce usage simultaneously affecting seller’s income at Pasar Segar Cinere, Kota Depok. Other than that, those factors partially also have the significant effect on the seller’s income.  Keywords: income, capital, length of business, location, e-commerce usage